Analysis of The Efficiency in the Productivity of Oilseeds exploited for Biodiesel in Brazil - Pereira da Silva, Simão; Sylvio Vieira da Costa, Alexandre (Revista Vozes dos Vales: Publicações Acadêmicas, 2024)
This research analyzes the productivity efficiency of soybean, corn, cotton, peanuts, oil palm, sunflower and canola, which are exploited in the production of biodiesel in Brazil. The data were treated using the technique Data Envelopment Analysis - DEA. Of the 23 soybean producing municipalities, 13 achieved efficiency (56%), however, from an environmental point of view, soybean is not the best choice for biodiesel production, as it has one of the lowest yields in oil per kg/ha (51%) and the lowest energy balance (1.3:1). However, its production scale ensures its participation in the biodiesel production chain. Of the 19 corn producing municipalities, six are efficient (31%), it is the second best average productivity (5,760 kg/ha), with a yield in kg/h of 14.17% and an energy balance of 1.42:1. In the seven municipalities producing cotton plume (processed), their productivity reaches 1/3 of the productivity of the five seed cotton producers (efficient, the third best average productivity with 4,290 kg/ha), yield in kg/ha of 45% and energy balance of 1.77:1. In peanuts, ten municipalities are efficient (37%). In oil palm, eight municipalities are efficient and this one has the best average productivity: 25,780 kg/ha, the second best yield in kg/ha (280%) and the best energy balance (5.6:1), in addition to generating two oils (the palm of the mesocarp and the palm kernel of the endocarp). In sunflower and canola, seven municipalities are efficient. The costs of inputs with SMFA (acronym in Portuguese for seeds, seedlings, fertilizers and pesticides) limit efficiency in productivity.